Atlas of Foot and Ankle Sonography. - Adler, Ronald S. (Wolters Kluwer Health, 2004)
Prepared by two leading experts in musculoskeletal ultrasound and a well-known podiatrist, this atlas is a complete guide to the use of ultrasound in the diagnosis of foot and ankle disorders. More than 160 illustrations display both normal ultrasound anatomy and a variety of common (and some uncommon) pathologic states. For each region of the foot and ankle, the atlas shows normal ultrasound anatomy and appearances of specific disorders. The authors compare the utility of ultrasound and MRI, particularly in detecting soft tissue injuries and foreign bodies. A chapter on ultrasound-guided ther.